2012
DOI: 10.1590/s1808-16572012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidade para a ocorrência de fasciolose na área experimental do Instituto Federal de Educação, Ciência e Tecnologia do Espírito Santo, IFES, Alegre, ES

Abstract: RESUMOUm estudo de vulnerabilidade para fasciolose foi conduzido na área experimental do Instituto Federal de Educação, Ciência e Tecnologia do Espírito Santo, IFES -Campus de Alegre, Espírito Santo. O Sistema de Informação Geográfica (SIG) foi utilizado para a geração de um Modelo Digital de Elevação (MDE) a partir do melhor interpolador para a área do estudo. A partir da análise do melhor interpolador, foi gerada a imagem matricial de declividade que foi reclassificada com o objetivo de discriminar apenas o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Subsequently, large numbers of cercariae are released by molluscs at the primary focus of the disease. Thus, having higher water availability, populations of molluscs may increase and expand foci of dissemination and vulnerability to disease, because the points are studied in the region of high prevalence for fasciolosis, as verified by Freitas et al (2012). This situation is considered serious, since the beginning of the rainy season cattle leaving a little feeding and face a high infection by intake metacercariae on abundant grassland.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, large numbers of cercariae are released by molluscs at the primary focus of the disease. Thus, having higher water availability, populations of molluscs may increase and expand foci of dissemination and vulnerability to disease, because the points are studied in the region of high prevalence for fasciolosis, as verified by Freitas et al (2012). This situation is considered serious, since the beginning of the rainy season cattle leaving a little feeding and face a high infection by intake metacercariae on abundant grassland.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Freitas et al (2012) conducted a study in an area with the presence of snails of the genus Lymnaea located in the Alegre city, and using variables such as waterbody, slope, floodplains and grasslands, generate vulnerability maps for the occurrence of the disease and attributed all sites sampled in areas of greatest vulnerability risk, with percentages ranging 25-31%. In another study, Freitas et al (2014) observed through a zoning distribution for risk areas for fasciolosis that 52.24% of the entire state is in areas at risk for occurrence and survival of F. hepatica.…”
Section: Resultsmentioning
confidence: 99%
“…Fatores como ausência de cobertura vegetal, a classe do solo, a intensidade de chuvas, dentro outros, associados à declividade, conduzirão a uma maior velocidade de escoamento, menor quantidade de água armazenada no solo e resultarão em áreas constantemente alagadas (FREITAS et al, 2012), gerando ambientes propícios para a proliferação de mosquitos (espécies de…”
Section: Mapas Temáticos Relacionados à Evolução Espacial E Temporal unclassified